Prediction, docking study and molecular simulation of 3D DNA aptamers to their targets of endocrine disrupting chemicals. Issue 16 (2nd November 2019) - Zhang, Weiwen; Yang, Fengxiao; Ou, Dejin; Lin, Ge; Huang, Aiyun; Liu, Nan; Li, Pinle
Abstract: Typical endocrine disrupting chemicals, including BPA (Bisphenol A), E2 (17-β-Estradiol) and PCB 72 (polychlorinated biphenyl 72), are commonly and widely present in the environment with good chemical stability that are difficult to decompose in vitro and in vivo . Most of the high-qualified antibodies are required as the key biomaterials to fabricate the immunosensor for capturing and detecting. As an ideal alternative, the short-chain oligonucleotides (aptamer) are essentially and effectively employed with the advantages of small size, chemical stability and high effectiveness for monitoring these environmental contaminants. However, the molecular interaction, acting site and mode are still not well understood. In this work, we explored the binding features of the aptamers with their targeting ligands. The molecular dynamics simulations were performed on the aptamer–ligand complex systems. The stability of each simulation system was evaluated based on its root-mean-square deviation. The affinities of these proposed ligands and the predicted binding sites are analyzed. According to the binding energy analysis, the affinities between ligands and aptamers and the stability of the systems are BPA > PCB 72 >E2 . Trajectory analysis for these three complexes indicated that these three ligands were able to steadily bind with aptamers at docking site from 0 to 50 ns and contributed to alteration of conformation of aptamers.